Comparative in vivo toxicity assessment places multiwalled carbon nanotubes at a higher level than mesoporous silica nanoparticles. (February 2017) - Rawat, Nidhi; Sandhya,; Subaharan, Kesavan; Eswaramoorthy, M; Kaul, Gautam
In the present work, we took two nanomaterials (NMs), mesoporous silica nanoparticles (MSNs) and multiwalled carbon nanotubes (MWCNTs), and compared their in vivo toxicity taking albino mice as a test animal model. Presently, conflicting data persist regarding behavior of these NMs with macromolecules like protein and lipid at the cellular level in cell lines as well as in animal models and this generated the interest to study them. The mice were treated orally with a single dose of 50 ppm MWCNTs and intraperitoneally with 10, 25, and 50 mg kg −1 body weight (BW) of MSNs and 1.5, 2.0, and 2.5 mg kg −1 BW of MWCNTs. Liver enzyme markers serum aspartate aminotransferase (AST), alanine aminotransferase, and alkaline phosphatase along with total protein (TP) levels were evaluated 7 days postexposure. No significant differences in organ weight indices or enzyme levels were observed between different treatment doses but there were significant differences between the treatment groups and the controls. Of the three enzymes assayed, AST displayed a peculiar pattern, especially in the MWCNTs intraperitoneally treated group. TP level was significantly increased in the orally treated MWCNTs group. The results showed that MWCNTs even at much smaller doses than MSNs displayed similar toxicity levels, suggesting that toxicity of MWCNTs is greater than MSNs.